Kerangka Teoritis Orisinal: Metode Perumusan Teori Inovasi Kurikulum Baru - Rahmat; Moh. Yahya Obaid; Herman; Samsuri; Halik; Anirwan (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Curriculum innovation at the educational unit level is often adopted reactively without a strong methodological foundation, causing reform to focus more on administrative compliance than on sustainable pedagogical transformation. This issue is particularly complex in Islamic Religious Education (PAI), which requires the ability to contextualize spiritual and moral values within students’ contemporary realities. This article aims to propose an original theoretical framework, namely the Ecological-Adaptive Curriculum Innovation Theory Formulation Method (MPEA). The study employs a conceptual Design-Based Research (DBR) approach integrated with qualitative Grounded Theory analysis. MPEA is formulated through four cyclical phases: deconstruction of constants, conceptual co-creation, prototyping through resonance testing, and organic theory formulation. The analysis indicates that MPEA has the potential to minimize structural resistance, reduce teaching burnout, and create space for teachers’ legitimate pedagogical ijtihad in developing contextualized content differentiation. This framework is expected to serve as a methodological compass for academics and policymakers in developing curriculum innovation theories that are deeply rooted in local philosophical values while remaining optimally adaptive to global change.